Pancreas size and exocrine function is decreased in young children with recent‐onset Type 1 diabetes. Issue 8 (17th June 2019) - Augustine, P.; Gent, R.; Louise, J.; Taranto, M.; Penno, M.; Linke, R.; Couper, J. J.; ,
Abstract: Aims: To measure pancreatic area and exocrine function in young children with recent‐onset Type 1 diabetes to determine whether the exocrine pancreas is also affected in the pathophysiology of early childhood diabetes. Methods: Thirty‐two children (14 boys) aged 5.5 (4.5, 7.3) median (IQR) years presenting with recent‐onset Type 1 diabetes and 90 controls (44 boys) of similar age had ultrasound imaging of the pancreas. Children with Type 1 diabetes were receiving insulin and were without ketosis. Transverse and longitudinal areas of the pancreas were measured by digitalized outline. Pancreatic faecal elastase‐1 was analysed using an enzyme‐linked immunosorbent assay kit in recent‐onset Type 1 diabetes and 38 first‐degree relative control children. Results: Pancreatic area and exocrine function were reduced in Type 1 diabetes. Mean transverse area (SD) in Type 1 diabetes was 6.82 cm 2 (1.61) vs. 8.31 cm 2 (1.74) in controls, adjusted estimate (95% CI) 1.45 (‐2.12, ‐0.79), P < 0.001; longitudinal area was 1.28 cm 2 (0.44) vs. 1.55 cm 2 (0.43), adjusted estimate (95% CI) ‐0.27 (‐0.45, ‐0.09), P = 0.003. Faecal elastase‐1 levels in Type 1 diabetes were 455 (323, 833) ug/g, median (IQR) vs. 1408 μg/g (1031, 1989) in controls, P < 0.001. Conclusion: Pancreatic area and accompanying subclinical exocrine function were reduced in very young children with recent‐onset Type 1 diabetes. This supports changes in the exocrine pancreas in the pathophysiology of Type 1 diabetes presenting in early life. What's new?: Pancreatic volume and pancreatic exocrine function are reduced in adults and adolescents with Type 1 diabetes. Pancreatic volume is intermediate in adult first‐degree relatives, both with and without islet autoimmunity. Young children with recent‐onset Type 1 diabetes also have reduced pancreatic size and accompanying subclinical exocrine dysfunction. The exocrine pancreas is affected in the pathophysiology of Type 1 diabetes presenting in early life.